2020
DOI: 10.1080/15538362.2020.1738975
|View full text |Cite
|
Sign up to set email alerts
|

Potent Antifungal Activity of Essential Oil from Morinda Citrifolia Fruits Rich in Short-chain Fatty Acids

Abstract: The fruit of the Morinda citrifolia species popularly known as "noni" has been widely used in folk medicine for diverse therapeutic purposes including in the treatment of infectious diseases. Given this, we tested the essential oil from M. citrifolia fruits obtained by hydrodistillation against fungi and bacteria. The oil was rich in short-chain fatty acids: octanoic acid (38.7%) and hexanoic acid (20.0%) were identified as the major constituents after analysis of oil by GC/MS. The oil showed antimicrobial act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In the present study, M. citrifolia EO was found to be effective against both Candida species, with an MIC of 0.25 mg/mL. This was in agreement with the study by Holanda et al [36], which also reported the high efficacy of M. citrifolia fruit EO against Candida species, namely C. albicans and C. utilise, with MIC values of 39 and 78 µg/mL, respectively. Remarkably, the same major components, octanoic (38.7%) and hexanoic (20.0%) acids, were revealed in the EO, as was previously reported by Jugreet and Mahomoodally (2020) for M. citrifolia EO investigated in the present study [11], although they varied in their percentages (octanoic acid (78.9%); hexanoic acid (11.3%)).…”
Section: Antifungalsupporting
confidence: 92%
“…In the present study, M. citrifolia EO was found to be effective against both Candida species, with an MIC of 0.25 mg/mL. This was in agreement with the study by Holanda et al [36], which also reported the high efficacy of M. citrifolia fruit EO against Candida species, namely C. albicans and C. utilise, with MIC values of 39 and 78 µg/mL, respectively. Remarkably, the same major components, octanoic (38.7%) and hexanoic (20.0%) acids, were revealed in the EO, as was previously reported by Jugreet and Mahomoodally (2020) for M. citrifolia EO investigated in the present study [11], although they varied in their percentages (octanoic acid (78.9%); hexanoic acid (11.3%)).…”
Section: Antifungalsupporting
confidence: 92%
“…Based on the results obtained from phytochemical analysis, the octanoic acids, hexanoic acids, and isobutyl pent-4-enyl carbonate are the main compounds (>91%) in M. citrifolia EO, as reported in previous studies [5,6]. However, it was also demonstrated in other investigations [27] that these same compounds represent less than 13% of the EO composition, which shows a strong variation in their chemical composition and consequently in their biological activity.…”
Section: Discussionmentioning
confidence: 52%
“…Bioassays were performed in commercial potato-dextrose-agar culture medium contained in Petri dishes (70 mm in diameter). Five concentrations (1,5,10,20, and 40 mg/mL) of noni EO and octanoic acid were diluted in a mixture of distilled water and 1.0 % (v/v) Tween 20 (Êxodo Científica, Hortolândia, São Paulo, Brazil). The test solutions were applied (at a volume of 200 µL) to cover the inner surfaces of Petri dishes (9 cm in diameter).…”
Section: In Vitro Activities Of Noni Eo Against S Cucurbitacearummentioning
confidence: 99%
See 1 more Smart Citation
“…The strong antimicrobial activity observed for the pH4-EO sample may be associated with the presence of the major compound α-santonin, a sesquiterpene that has been used as an effective drug against infectious diseases caused by worms, which was first isolated from the flower bud of Artemisia santonica (Wang et al, 2019). Activity for the pH4-EO sample can also be attributed to the presence of 5-methylhexanoic and nonanoic acids as oils rich in short-chain fatty acids exhibit strong antimicrobial activity (Holanda et al, 2020). The activities of the pH7-EO and pH10-OE samples were considered moderate to weak for all microorganisms tested, with a MIC that varied between 625 µg/ml and 2500 µg/ml for both oils.…”
Section: Resultsmentioning
confidence: 99%